Roles of Serum Amyloid A 1 Protein Isoforms in Rheumatoid Arthritis. (March 2022) - Leung, Elaine Laihan; Lai, Huan-Ling; Li, Run-Ze; Pan, Hu-Dan; Jiang, Ze-Bo; Li, Ying; Duan, Fu-Gang; Xu, Jia-Hui; Zhang, Yi-Zhong; Shi, A-Xi; Wei, Chun-Li; Zhang, Fang-Yuan; et al.
Abstract: Secondary amyloid A amyloidosis, a lethal complication, is induced when acute or chronic infection coexists with over-secretion of the serum amyloid A 1 (SAA1) protein and deposition in key internal organs. Previously, using the whole-exome sequencing method, we identified a novel deleterious mutation SAA1.2 in rheumatoid arthritis (RA) patients. However, the role of SAA1 in RA pathogenesis and its complications remains unknown. The purpose of this study was to determine the pathogenetic roles of SAA1 protein isoforms in RA progression. We modified an experimental adenovirus infection protocol to introduce SAA1.2 gene alleles into the knee joints of mice and used SAA1.3 and SAA1.5 as controls. Micro-computed tomography analysis was applied to determine changes in bone morphology and density. Immunohistochemical (IHC) analysis, flow cytometry, enzyme-linked immunosorbent assay (ELISA), and real-time polymerase chain reaction (RT-PCR) were used to investigate disease progression and cytokine alterations in the course of adenoviral SAA-induced knee joint inflammation and bone destruction. We found that the arthritis-inducing effect of SAA1.2 transcription in the knee joints and mutant SAA1 protein secretion in blood resulted in the stimulation of immune responses, leading to CD8 + T cell and pro-inflammatory cytokine elevation, such as interleukin (IL)-6, IL-22, matrix metalloproteinase (MMP)-3, MMP-9, with subsequent synovial inflammation and bone destruction. These findings indicate that SAA1 protein isoforms, particularly SAA1.2, play a significant role in the induction and progression of RA and may have potential value in the early diagnosis and severity prediction of RA.